FAKSI SEBAGAI STRATIFIKASI SOSIAL DALAM FILM DIVERGENT PRODUKSI SUMMIT ENTERTAINMENT - TILAAR, SOFYAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â  This research entitled â€œStratifikasi Sosial dalam FilmDivergent produksi Summit Entertainmentâ€. Present as a reqruitment for getting a degree S.SÂ Â Â Â Â Â Â Â Â Â Â  The objectives of this research are to identify, describe, and analyze, social stratification in the film Divergent. The writer uses the theory of Lenski and Lenski and also Parsons to analyze the data and to find out the stratification. This research has been done by using descriptive method.Â Â Â Â Â Â Â Â Â Â Â  The methodology conducted consist of 3 phases those are Preparation, Data Collection, and Data Analysis. The data were taken from the Film Divergentthrough intrinsic elements such as character, action, and expression.The research findings show that â€œSocial Stratificationâ€is admitted alive by Neil Burger through â€œFilm Divergentâ€. It depicted in the interaction among character, expression, and action in the film.Keyword: Divergent, social stratification, character, expression, action, faction.